Prognostic analysis of hepatocellular carcinoma with macrovascular invasion after liver resection and a successful case of conversion therapy - Ji, Mengling; Zou, Hao; Shu, Baojun; Liu, Guoping; Zhang, Bingyuan; Xu, Zejiang; Pang, Fanfan; Cheng, Mengxing; Sun, Yafei; Du, Ting; Sun, Chuandong; Zhu, Chengzhan (Frontiers in Surgery, 2022)
Objective: Macrovascular invasion (MVI) is an important factor leading to poor prognosis in hepatocellular carcinoma (HCC). Liver resection may offer favorable prognosis for selected patients with HCC. This study aimed to analyze the prognostic factors of HCC with MVI after liver resection as well as demonstrate a case of conversion therapy in an HCC patient with portal vein tumor thrombus (PVTT). Methods: A total of 168 HCC patients with MVI who underwent primary liver resection at the Affiliated Hospital of Qingdao University between January 2013 and October 2021 were enrolled in the study. Clinicopathological data were collected retrospectively. Univariate and multivariate regression analyses were used to investigate the risk factors influencing recurrence and overall survival. Additionally, conversion therapy with drug-eluting bead transarterial chemoembolization (D-TACE), and sorafenib plus sintilimab treatment was performed in an HCC patient with PVTT. Results: Among the 168 patients with HCC, 11 were diagnosed with hepatic vein tumor thrombosis, and the rest were diagnosed with PVTT. The 1-year disease-free survival rate was 37.5%, and the 3-year overall survival rate was 52.7%. Univariate and multivariate regression analyses revealed that HBsAg positivity, alpha-fetoprotein (AFP) level ≥400 ng/ml, liver capsule invasion, and tumor number ≥2 were independent prognostic factors for tumor recurrence, whereas HBsAg positivity was an independent risk factor for overall survival. Postoperative prophylactic medication did not significantly prolong the recurrence time. The median survival time (MST) after tumor recurrence was 13.4 months. In the patient treated with conversion therapy, the tumor gradually shrank and was eventually surgically resected. Conclusions: This study identified the independent prognostic and risk factors associated with recurrence and overall survival in HCC patients with MVI. Additionally, we successfully performed conversion therapy in an HCC patient with PVTT. The findings would help identify patients at high risk of recurrence and indicate that combined therapy may prolong the survival of HCC patients with PVTT.